Digital Fundraising Strategy Analysis In Increasing Baznas Income In Sampang District - Maulana, Rahman (Journal of English Language and Education, 2025)
Sampang Regency ranked highest in poverty in East Java in 2020 and 2021, with poverty percentages of 22.47% and 23.72%. Zakat is a form of worship that has a very important, strategic and decisive position, both in terms of Islamic teachings and in terms of community development. In this digital era, everything has become smart, smarter, more time-saving and more accurate and people tend to change their style and behavior to digital behavior and lifestyle in every activity and transaction carried out, including in terms of paying zakat.The researcher in conducting this research used a qualitative approach. Qualitative research means the process of exploring and understanding the meaning of individual and group behavior, describing social problems or humanitarian problems.This study shows how the implementation of the digital fundraising strategy at BAZNAS Sampang Regency, how effective the implementation of the digital fundraising strategy at BAZNAS Sampang Regency has not been and what are the supporting and inhibiting factors faced by BAZNAS Sampang Regency.